Functional complexity of switch-reference clauses in Santiago del Estero Quichua - Juanatey, Mayra Ayelen (2025)
Complex sentences display a relation between two or more events, and different languages have different strategies to deal with the encoding of the participants in each event. This study explains how referent tracking is maintained in switch-reference clauses in Santiago del Estero Quichua (Quechua, Argentina). However, since some data cannot be explained in terms of the marking of the (dis)continuity of referents at the sentence level, a functional perspective that contemplates phenomena of syntax-discourse interfaces is needed in order to fully understand the use of switch-reference clauses in this particular language. This is not an exception in switch-reference systems across languages of the world. The systems under study are usually functionally complex as they may provide information about the congruence between eventualities, with referential continuity being only one of their sub-functions. Therefore, these systems are closely linked to the marking of referential and temporal meanings. According to the findings of this study, the switchreference system in Santiago del Estero Quichua plays an important role in maintaining discourse coherence. This property of switch-reference clauses in the language is crucial for comprehending their role, not only in complex syntax but also in the organization of discourse.